KAHOOT IN MARITIME ENGLISH TEACHING: ITS IMPACT ON NAUTICAL SCIENCE CADET’S ORAL REPRODUCTION AND VOCABULARY - Sartini, Sri (Universitas Ahmad Dahlan, 2020)
This type of research was Participatory Action Research using the Denzin and Lincoln (2005) model which consists of the Kahoot pre-action cycle and post-action cycle. This study aimed to examine the use of Kahoot Platform in Maritime English learning. It improved the speaking skill of nautical science cadets by the increasing number of maritime vocabularies as an indication. The results of this study described that the use of Kahoot quiz made learning experienced in the classroom very interactive, interesting, and effective, because of the two cycles carried out increased from the beginning of the cycle to the next cycle marked by the increasing number of correct answers done by the cadets. Thus, their vocabulary mastery increased as well. Kahoot not only increased vocabularies that supported cadet?s speaking skill initiated by the correct oral reproduction, but also increased cadet?s enthusiasm in learning Maritime English. In conclusion, the use of online gamification-based Kahoot quiz toward nautical science cadets at Sekolah Tinggi Maritim Yogyakarta had a significant impact on vocabulary mastery for effective communication skills.